Sustained linear growth and preserved renal function in 10‐year survivors of pediatric liver transplantation. (13th March 2015) - Lee, Sanghoon; Kim, Jong‐Man; Choi, Gyu‐Seong; Kwon, Choon Hyuck D.; Choe, Yon‐Ho; Joh, Jae‐Won; Lee, Suk‐Koo
Summary The aim of this study was to characterize the clinical outcomes of children and adolescents who achieved survival of more than 10 years following liver transplantation (LT) in a single center in Korea. From June 1996 to October 2003, 57 pediatric LTs were performed. The medical records of 44 patients who had survived more than 10 years were reviewed retrospectively. Median age of patients at LT was 0.8 years. Forty‐one patients received living donor LT, and three patients received deceased donor LT. Biliary atresia was the most common indication (65.9%). Thirty‐five patients were on tacrolimus monotherapy at 10 years post‐LT with a mean trough level of 2.73 ng/ml, and five patients were maintaining stable graft function without any immunosuppression. There were no patients receiving antihypertensive medication and one case of diabetes mellitus. Renal dysfunction was seen in two patients (4.5%), while none required renal replacement therapy. Mean height z‐score prior to LT was −1.35 and at 10 years post‐transplant was 0.05. Good linear growth was sustained in this cohort throughout the 10 years, approaching the 50th percentile. Also, there were remarkably low incidences of renal dysfunction and patients requiring medications for glycemic or hypertensive control, all hallmarks of continued use of immunosuppressive agents.